MEREC - Guarda: An Energy and Resource Efficiency Process undermined by the early stages of a democratic setting. - Ramos, Cátia; Couceiro, Mauro Costa; Brito, Nelson (International Planning History Society Proceedings, 2016)
This article focuses on the historical background which lead to the implementation of an EUA programme in a European country; a programme designed for developing countries. To that end, we seek to discern, how 1980's Managing Energy and Resource Efficient Cities (MEREC) methodology has perpetuated in urban planning and architecture practice as well as in the discourses of its stakeholders. Guarda is a medieval border town (1050m) in the hinterland of Portugal, far away from the impact of metropolitan areas, such as Lisbon or Porto. Guarda kept a balanced urban growth over the years, but demography and key sectors of the economy changed profoundly after the Portuguese democratic revolution (1974). Serving as an early experience towards city resilience and sustained development, MEREC was a programme developed by the United States Agency for International Development (USAID). Inspired by the work of Richard Meier (1974), MEREC answered to the growing concerns triggered by the 1970s energy crisis and its consequences. Amid a rapid urbanisation and population growth, increased energy costs and pressure on natural resources, MEREC targeted cities in developing countries which could adopt preventive approaches towards resource efficiency. However, instead of concentrating its efforts on metropolitan areas, MEREC aimed at the development of secondary cities, where most of the growth had yet to come. From 1983 to 1985, MEREC established a comprehensive planning process, involving Guarda Municipality, central and regional agencies and the know-how of Portuguese universities and private consultants. MEREC identified the city's problems in water supply, urban waste, urban management, changes in local building materials used and scattered urbanisation. Several of these problems had been overcome with the project's completion, the development of Guarda's master plan, research technology, and awareness campaigns. USAID-MEREC advisors considered the results achieved in Guarda as rewarding. Architect Maria Castro (1989) points out the clarity achieved in the decision-making processes for urban planning and management during the MEREC programme. However, as she notes, discourses and institutional support changed after MEREC. MEREC’s methodology was somehow thrown away, suggesting a lack of planning culture among local political powers, unwilling to redirect resources. MEREC happened ten years after Portugal's dictatorship had ended, when the country was committed to the world as a democratic country, facing political and economical instability until its accession to the European Economic Union (EEC), as well as, undergoing deep socio-cultural transformations and striving for development. From 1986 onwards, MEREC programme was hampered by a democratic setting that aimed for development in more immediate ways, regardless of the resource-efficiency strategy proposed.